Is atrial fibrillation a risk factor for in-hospital cardiac arrest?: a Swedish retrospective cohort study. Issue 6 (30th June 2018) - Ryden, Alexander; Engdahl, Johan; Claesson, Andreas; Nordberg, Per; Ringh, Mattias; Hollenberg, Jacob; Djärv, Therese
Abstract : Introduction: Atrial fibrillation (AF) is associated with increased morbidity and mortality. Recent findings suggest that AF is also associated with out-of-hospital cardiac arrest. However, whether that association can be generalised to in-hospital cardiac arrests (IHCAs) is still unknown. Aims: To examine whether there is a stronger association with IHCA among hospitalised patients with AF compared with patients without AF. Materials and methods: All adult patients admitted to the Karolinska University Hospital, Stockholm, Sweden during 2014–2015 were included. Data were drawn from their medical file and matched against the Swedish Registry for Cardiopulmonary Resuscitation. Patients who were documented as ever having the International Classification of Diseases, 10th revision code I48 prior to the current hospitalisation were categorised to the AF group and the remaining were categorised to the non-AF group. The primary outcome was occurrence of an IHCA. Results: In all, 102 416 patients were included. Among these, 10% had been diagnosed with AF and <1% (n=326) suffered from an IHCA, only 42 (13%) had a VF/VT. In a multivariable model adjusting for sex, age, CharlsonComorbidity Index score and whether the patients had been admitted electively or urgently, having AF was significantly associated with IHCA (OR 1.760; 95% CI 1.356 to 2.269; p<0.001). Conclusions: Within this observational cohort study, patients with AF had a stronger association with IHCA than patients without AF. AF might be an independent risk factor for IHCA.